Superoxide- and semiquinone-linked activation of molecular hydrogen in metal-catalyst-free solution - Ishibashi, Toru; Harunari, Enjuro; Ishihara, Genki; Niiyama, Tetsushi; Noda-Urata, Mami; Komori, Nobuaki (Frontiers in Molecular Biosciences, 2025)
The therapeutic effects of molecular hydrogen (H2), particularly in ischemia-reperfusion (I/R) injury and deleterious inflammation, have been increasingly attributed to its modulation of redox balance. However, the precise molecular mechanisms underlying H2-medated redox modulation, particularly in mitochondrial reverse electron transfer (RET)-driven superoxide (O2•-) generation, remain unclear. Here we show that under membrane-less in-solution conditions, H2 modulates O2•- kinetics in ways consistent with a tunneling-assisted electron transfer involving SQ radicals, without catalytic metals or hydrogenases. Using enzymatic (xanthine oxidase/hypoxanthine; XO/Hx) and non-enzymatic (potassium superoxide; KO2) systems combined with the O2•–specific chemiluminescent probe, 2-methyl-6-p-methoxyethynyl-imidazopyrazinone (MPEC), we observed bell-shaped and U-shaped O2•- kinetics as a function of H2. In Q-free assays, O2•- appeared to activate H2, yielding a clear bell-shaped kinetic profile compatible with tunneling-assisted electron transfer from H2 to O2•-. When Q was present, distinct U-shaped profiles emerged, consistent with Q•–mediated electron buffering followed by H2 activation. Electron spin resonance (ESR) radical scavenging experiments and quantitative high-performance liquid chromatography (HPLC) analyses confirmed transient semiquinone-mediated redox cycling leading to the formation of ubiquinol (QH2). Collectively, these in-solution data support a metal-free pathway for H2 participation in Q redox cycling that is compatible with tunneling-assisted electron transfer under defined in vitro conditions. These findings demonstrate the chemical feasibility of H2-driven Q reduction in-solution; the in vivo relevance remains to be determined.